Prospective assessment of a palliative care tool to predict one-year mortality in patients with acute coronary syndrome. Issue 3 (1st April 2017) - Moretti, Claudio; Iqbal, Javaid; Murray, Scott; Bertaina, Maurizio; Parviz, Yasir; Fenning, Stephen; Quadri, Giorgio; Gunn, Julian; D'Ascenzo, Fabrizio; Marra, Sebastiano; Moiraghi, Corrado; Riccardini, Franco; et al.
Abstract: Background: Identifying patients with acute coronary syndrome (ACS) who are approaching the end of life and who may not benefit from an aggressive interventional approach is important but clinically challenging. The Gold Standards Framework (GSF) prognostic guide was developed using multidimensional criteria to identify cancer patients who could benefit from end-of-life care. We assessed the utility of the GSF to predict one-year mortality in ACS patients. Methods: ACS patients admitted between May 2012 and July 2013 at the three participating cardiac centres in Europe were enrolled. Patients were assessed during admission using the GSF, the Global Registry of Acute Coronary Events (GRACE) score, the age, creatinine, ejection fraction (ACEF) score and the New York Percutaneous Coronary Intervention (NY-PCI) risk score. The pre-specified primary outcome was all-cause mortality at one year; secondary outcomes were cardiovascular death, non-cardiovascular mortality, re-hospitalisation for ACS and re-hospitalisation for non-ACS causes. Results: Six hundred and twenty-nine ACS patients were enrolled and one-year follow-up data was available for 626 patients. Fifty-two patients (8.3%) met GSF criteria for end-of-life care. These patients were older, predominantly female, had lower body mass index (BMI), and were less likely to receive angiography (75% vs 95%, p <0.001) and angioplasty (60% vs 77%, p =0.005) compared with patients who did not meet GSF criteria. Patients meeting GSF criteria had higher one-year all-cause mortality (42.3% vs 4.5%, p <0.001), cardiovascular mortality (15.4% vs 2.8%, p <0.001) and non-cardiovascular mortality (26.9% vs 1.7%; p <0.001). Multivariate analysis confirmed that meeting GSF criteria independently predicted all-cause mortality. Conclusion: GSF is a multidimensional tool which may be used to identify ACS patients that are at high risk of death and may benefit from end-of-life care.